Increase in Maternal Mortality and Prematurity During the Covid-19 Pandemic in Chile [Aumento de Mortalidad Materna y de Prematuridad Durante Pandemia de Covid-19 en Chile] - Gutierrez-Pinto, J; Haye-Morales, M; Gonzalez-Perez, R (Ediciones Doyma, S.L., 2023)
Introduction: At the third year of the pandemic in Chile, the reported cases of COVID-19 reached 4,769,638 and 61,725 deaths (1.4%), with 93% of the population with a complete vaccination schedule (17,686,528). Aim: The purpose of this study is a brief communication on the impact of the SARS-CoV-2 pandemic on maternal, perinatal and prematurity mortality in Chile. Method: The national database of the Informatics Department of the Ministry of Health of Chile (DEIS), and the information reported from the official WHO website were used. All births, general and fetal deaths from January 1990 to September 2022 were included. A comparison is made between the basic maternal and perinatal indicators of the last 30 years and those of the years of the pandemic. Results: From March 2020 to September 2022, approximately 61,000 people died in Chile with a diagnosis associated with COVID-19, 17% of the general mortality for the period (approx. 364.000 deaths). An acceleration in the historical trend towards a decrease in the overall birth/death ratio was observed from 1.9 pre-pandemic to 1.4 during the third year of the pandemic. Maternal Mortality Ratio in 2020 (28.1 × 100,000) increased compared to 2019 pre-pandemic (19.1) or the simple historical trend line projected for 2020 (18.0) by 56%. Prematurity under 37 weeks of gestation increased from 8.5% (2019) to 9.5% for the years 2021 and 2022. Neonatal mortality in the first 28 days remained stable at 9 per thousand births during the 3 years of the pandemic and fetal mortality (>21 weeks) had a slight increase to 4.7 per thousand (year 2020) in relation to 3.4 in 2019. Conclusions: In Chile, an increase of approximately 56% in maternal mortality occurred in the first year of the SARS-CoV-2 pandemic. In the second year, a significant increase in late prematurity and a slight increase in fetal mortality were observed. These findings have been reported in the reviews and latest updates of the year 2022. © 2023